Effect of crude extract and essential oil of Cordia verbenacea in experimental periodontitis in rats - Fernanda Vieira Ribeiro; Guilherme Emerson Barrella; Renato Corrêa Viana Casarin; Fabiano Ribeiro Cirano; Mary Ann Foglio; Suzana Peres Pimentel (Universidade Estadual de Campinas, 2015)
Aim: To evaluate the effect of crude extract and essential oil of Cordia verbenacea (C.V.), systemically administered, on ligature-induced periodontitis in rats. Methods: Periodontitis was induced in 54 Wistar rats: one of the first mandibular molars was randomly assigned to receive a ligature, whereas the contralateral molar was left unligated. Then, animals were randomly assigned to one of the following groups: non-treatment group (n=18): animals that received 10 mL/day of vehicle; C.V. extract group (n=18): animals that received 100 mg/kg/day of crude extract of C. verbenacea; and C.V. essential oil group (n=18): animals that received 100 mg/kg/day of essential oils free of C. verbenacea. All therapies were administered orally 3 times daily, for 11 days. Next, the animals were sacrificed, and the specimens were processed for morphometric analysis. Bone loss was determined on the buccal surface of the lower first molars by the distance of the cementoenamel junction from the alveolar bone. Results: Both extract and essential oil of C. verbenacea orally administered decreased alveolar bone loss in the ligated teeth when compared with the non-treated group (p<0.05). Conclusions: The present study demonstrated that systemic administration of both formulations of Cordia verbenacea may attenuate the progression of ligatureinduced periodontitis.